АDMINISTRATIVE AND LEGAL SUPPORT OF THE LEGAL REGIME OF MARTIAL LAW IN UKRAINE - Pashynskyi, V.; Stupak, D. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2023)
The issue of administrative and legal support of the legal regime of martial law was considered. Scientific views on such legal categories as "legal provision" and "administrative-legal provision" in various spheres of social relations have been studied. The concept of "administrative and legal support of the legal regime of martial law" is considered. The key features of the administrative and legal support of the legal regime of martial law are established, namely: the support of the specified legal regime is carried out by special entities whose powers are defined by legislation; regulated by the norms of administrative law; implemented using special tools (mechanisms, measures); the activity of public administration subjects consists in the adoption of laws, subordinate regulatory legal acts and their implementation. Based on the results of the research, the author's definition of the concept of administrative and legal support of the legal regime of martial law is proposed as the activity of authorized subjects of public power in relation to the legal regulation of social relations, legal support for the implementation of the measures of the legal regime of martial law, regulated by the norms of administrative law, with the aim of protecting human rights and freedoms. defense of the state in case of armed aggression or threat of attack, danger to the state independence and territorial integrity of Ukraine. It has been established that the essence of the administrative and legal provision of the legal regime of martial law is the provision of conditions for achieving the goals of its introduction, as well as the provision of regulation, implementation, protection and protection of social relations in the conditions of martial law.
Keywords: legal support, administrative-legal support, legal regime of martial law, administrative-legal support of the legal regime of martial law, signs of administrative-legal support of the legal regime of martial law